ANALISIS TEKNIK SCAT SINGING ELLA FITZGERALD DALAM LAGU ALL OF ME - Dyah Paramitha, Monica; Evelin Limbong, Helena; Hardiarini, Caecilia (Jurnal Penelitian Musik, 2024)
The term “jazz” has a variety of meanings because it has been used to describe various styles of music. But, there are two aspects that almost all jazz styles have in common—swing feeling and improvisation. In jazz music, vocal improvisation has the same definition as an instrument improvisation, where the musician or vocalist creating melodies based on pre-exisiting chord progressions. Based on the writer's personal experience in a jazz community in Indonesia, singers have difficulty getting information to learn vocal improvisation or scat singing. This research was started on October 2020 and the writer used a qualitative approach to investigate Ella Fitzgerald’s scat singing technique. Fitzgerald’s scat singing skills consists of several interesting musical elements to learn such as motives and motivic development, chordal approach, and chromatic approach. For singers who want to learn about scat singing and it sounds interesting like Fitzgerald, must have at least a basic musical theory, basic vocal technique and ability mimicking the sound of musical instruments using the nonsense syllables.